Institutional change - Mazur, Stanisław (Journal of Public Governance, 2014)
The author attempts to describe the phenomenon of institutional change. He discusses two different approaches to institutional change and its explanation, and presents his definition of institution and of the interdependence between agent and institution. He also discusses the types and mechanisms of institutional change and its unintended consequences.